Presynaptic Molecular Determinants of Quantal Size - Takamori, Shigeo (Frontiers in Synaptic Neuroscience, 2016)
The quantal hypothesis for the release of neurotransmitters at the chemical synapse has gained wide acceptance since it was first worked out at the motor endplate in frog skeletal muscle in the 1950s. Considering the morphological identification of synaptic vesicles at the nerve terminals that appeared to be homogeneous in size, the hypothesis proposed that signal transduction at synapses is mediated by the release of neurotransmitters packed in synaptic vesicles that are individually uniform in size; the amount of transmitter in a synaptic vesicle is called a quantum. Although quantal size – the amplitude of the postsynaptic response elicited by the release of neurotransmitters from a single vesicle – clearly depends on the number and sensitivity of the postsynaptic receptors, accumulating evidence has also indicated that the amount of neurotransmitters stored in synaptic vesicles can be altered by various presynaptic factors. Here, I provide an overview of the concepts and underlying presynaptic molecular underpinnings that may regulate quantal size.